Effects of annealing in air on microstructure and hardness of hydroxyapatite ceramics. (25th May 2021) - Zhu, Wenliang; Imamura, Hayata; Marin, Elia; Adachi, Tetsuya; Miyamoto, Nao; Yamamoto, Toshiro; Kanamura, Narisato; Pezzotti, Giuseppe
Abstract: In this study, microstructural variation of hydroxyapatite (HAp) ceramics upon thermal treatment in air at different temperatures was investigated by x-ray diffraction patterns, Raman and x-ray photoelectron spectroscopies. The results revealed a significant dependence of the microstructure of nonstoichiometric HAp on temperature, because of the competition between hydroxylation and different kinds of dehydroxylation at different temperatures, and a gradual increase in material hardness with annealing temperature because of structural reconstruction. In summary, a suitable thermal treatment can effectively tailor microstructure and defect contents, as well as chemical composition and mechanical hardness of HAp ceramics.